The National Ignition Facility Diagnostic Set at the Completion of the National Ignition Campaign, September 2012. (1st February 2016) - Kilkenny, J. D.; Bell, P. M.; Bradley, D. K.; Bleuel, D. L.; Caggiano, J. A.; Dewald, E. L.; Hsing, W. W.; Kalantar, D. H.; Kauffman, R. L.; Larson, D. J.; Moody, J. D.; Schneider, D. H.; et al.
Abstract: At the completion of the National Ignition Campaign (NIC), the National Ignition Facility (NIF) had about 36 different types of diagnostics. These were based on several decades of development on Nova and OMEGA and involved the whole U.S. inertial confinement fusion community. In 1994, the Joint Central Diagnostic Team documented a plan for a limited set of NIF diagnostics in the NIF Conceptual Design Report. Two decades later, these diagnostics, and many others, were installed workhorse tools for all users of NIF. We give a short description of each of the 36 different types of NIC diagnostics grouped by the function of the diagnostics, namely, target drive, target response and target assembly, stagnation, and burn. A comparison of NIF diagnostics with the Nova diagnostics shows that the NIF diagnostic capability is broadly equivalent to that of Nova in 1999. Although NIF diagnostics have a much greater degree of automation and rigor than Nova's, new diagnostics are limited such as the higher-speed X-ray imager. Recommendations for future diagnostics on the NIF are discussed.